The Assessment of the Occurrence of Benign Hypermobility Joint Syndrome in Physiotherapy Students - Ewelina Żyżniewska-Banaszak; Hanna Tchórzewska-Korba; Magdalena Gębska; Katarzyna Weber Nowakowska; Katarzyna Leźnicka; Kuba Żyżniewski (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2017)
The occurrence of connective tissue disorders is an important factor for development of occupational diseases in professions requiring a non-ergonomic and often static load of the musculoskeletal system. Symptoms of the connective tissue disorders appear at different ages. The diagnosis of hypermobility is an important problem due to the lack of uniform diagnostic criteria. The aim of this paper is to evaluate the incidence of joint hypermobility and its relation with a history of injuries and the level of physical activity in Physiotherapy students. The study involved 143 students (69% female, 31% male) aged 18 to 27 years (M = 20.7; SD = 1.43). The assessment of the occurrence of Benign Hypermobility Joint Syndrome (BHJS) syndrome was performed using the Beighton and Brighton scale. Among the surveyed students almost 82% of the women and just over 18% of the men fulfilled the diagnostic criteria for the diagnosis of hypermobility. A significant difference was also observed in the physical activity of the students. Among those who showed no signs of hypermobility exactly half of the participants trained sports as amateurs, while in the group of people with hypermobility the proportion was lower by nearly half. BHJS was not related to injuries and operations in the study group.